The Relationship Between Academic Stress, Irritating Food and Beverage Consumption and Dietary Regularity to Incidence of Functional Dyspepsia - Putra, Andry Cahaya; Utama, Lalu Buly Fatrahady; Azmi, Fahriana; Santosa, I Ketut Arya (Jurnal Biologi Tropis, 2025)
Anyone can have dyspepsia, a complaint that is frequently seen in clinical practice. Organic and functional dyspepsia are the two categories of dyspepsia cases. Functional dyspepsia accounts for the majority of dyspepsia cases. This study was conducted to determine the relationship between academic Stress, consumption of irritating food and beverages, and regularity of eating patterns on the occurrence of functional dyspepsia in first-year students of the Faculty of Teacher Education at Muhammadiyah University of Mataram. The research used an observational analytical quantitative method using a cross-sectional research design. Data collection was accomplished using simple random sampling using a questionnaire. 72 samples in total, based on inclusion and exclusion criteria, were used in this investigation. The data was gathered on September 2024. The chi-square test was used to examine data statistics. The findings demonstrated a substantial correlation (p-value = 0.001) between the incidence of functional dyspepsia and academic stress. A substantial correlation (p-value = 0.001) was found between the incidence of functional dyspepsia and the consumption of irritating foods and beverages. With a p-value of 0.001, there was a significant correlation between the frequency of functional dyspepsia and the regularity of eating behaviors. Conclusion: In first-year students at Muhammadiyah University of Mataram's Primary School Teacher Education Faculty, functional dyspepsia is associated with academic stress, the consumption of irritant foods and drinks, and regular eating habits.